Fluorescent photoaffinity probes for mitotic protein kinase Aurora A. Issue 16 (15th August 2015) - Lavogina, Darja; Kisand, Katariina; Raidaru, Gerda; Uri, Asko
Graphical abstract: Abstract: We combined the advantages of the selective inhibitor VX689, the bisubstrate-analogue conjugate approach, and photoreactive amino acids to develop 8 photoaffinity probes for Aurora A. The most efficient compounds possessed one-digit nanomolar K D values in the equilibrium binding assay, inhibited Aurora A at elevated concentrations of ATP in the phosphorylation assay in the presence of TPX2, and formed covalent complexes with the recombinant kinase or Aurora A in HeLa cells upon UV-irradiation. The recognition of the correct target by the probes during formation of the covalent complex in the biochemical assay and in situ was demonstrated by competition experiments using the non-labelled inhibitors VX689 and MLN8237.